Status and Rights of Illegitimate Children - Al Insyirah, Jihan Aisyah; Sanjaya, Umar Haris (Notaire, 2025)
In Indonesia, there are differences in the inherent status and alimentation rights between legitimate and illegitimate children. Illegitimate children only have the civil relationship with their mothers amd to ensure illegitimate children have a legal relationship with their biological father, a legal action is required as stated in the Constitutional Court Decision Number 46/PUU-VIII/2010, through DNA tests or other scientific methods. Concurrently, there is a case where a man recognized as the biological father of a child, without reference to DNA test or other scientific methods. This research aims to find about the status of illegitimate children in Indonesia and determine the impacts of their status on their entitlement to rights of alimony. This writing uses a normative juridical legal research method that is guided by legal rules or norms. The approach methods used are case approach and statutory approach. The source of this legal research material uses primary legal materials, secondary legal materials and tertiary legal materials. Data collection uses a qualitative data analysis method. namely by describing legal issues found through literature research using relevant regulations. The results of this study are to examine the status and alimentation rights that arise based on DNA test and other scientific evidence.